The Effectiveness of Cognitive-Behavioral Training on Meta-Worry and Social Adjustment of University Students - Atiyeh Asadi; Ali Naseri (مجله علوم پزشکی صدرا)
Introduction: Students are considered valuable assets and key members of society, playing a pivotal role in shaping the future of the country. Given the prevalence of emotional fluctuations, anxiety, and worry among students, this study aimed to investigate the effectiveness of cognitive-behavioral training on meta-worry and social adjustment of University students.Methods: This study employed a quasi-experimental design with pre-test, post-test, and control group. The statistical population included all undergraduate students enrolled in 2022 at the Islamic Azad University, Kerman Branch. A total of 72 students were selected through a multi-stage cluster sampling method and randomly assigned to two groups of 36. The intervention group received cognitive-behavioral training in nine sessions, each lasting 60 to 90 minutes. The research instruments included Wells’ Meta-Worry Questionnaire and Bell’s Adjustment Inventory. Data were analyzed using multivariate analysis of covariance (MANCOVA).Results: The results indicated a significant difference between the mean scores of meta-worry and social adjustment in the experimental and control groups during the post-test phase, with a 95% confidence level (P<0.05). Cognitive behavioral training led to a 13.06% reduction in meta-worry scores and a 19.87% increase in social adjustment scores in the experimental group.Conclusion: Cognitive behavioral training could be effectively utilized to reduce psychological issues among students and enhance their social adjustment.